Georgia - Lerner Publications Company. Geography Dept. (Minneapolis : Lerner Publications Co., 1993)
Discusses the geography, history, politics, economics, and ecology of the former Soviet republic Georgia.
Includes index.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
7.2
4-6
Keywords: Georgia (Republic) -- Juvenile literature; Georgia (Republic); Georgia (Republic)